Evaluating the efficiency of stone columns in mitigating liquefaction risks and enhancing soil bearing capacity: A case study - BZIAZ, Mohamed; BAHI, Lahcen; OUADIF, Latifa; BAHI, Anas; MANSOURI, Hamou (International Journal of Innovative Research and Scientific Studies, 2023)
Several processes allow the improvement of soils such as vibrocompaction, stony columns, static horizontal compaction etc. These processes reduce the risk of liquefaction potential and making it possible to build on this type of soil when the space restriction require it. Stone columns are a recognized method of soil improvement, which consists of creating large diameter columns using special vibrators with granular filling materials introduced into the ground. The objective of this work is to evaluate the effectiveness of stone columns, made in a seismic zone containing liquefiable materials, with regards to the reduction of the risk of liquefaction and the improvement of the bearing capacity of the soil. The approach followed is the exploitation of geotechnical investigation tests (CPT Cone Penetration Test), (SPT: Cone Penetration Test, (pressuremeter tests), carried out before and after soil treatment. This study showed that the network of gravelled columns produces an enhanced soil improvement effect by improving the modulus of elasticity of the soil and reducing settlement and the risk of liquefaction after treatment. The process allows for the improvement of the geotechnical characteristics of its soils, making it possible to build infrastructure and development projects in the area.